RARE AND ENDANGERED ROVE BEETLES OF UKRAINE: EMUS HIRTUS LINNAEUS, 1758 (COLEOPTERA: STAPHYLINIDAE) - Glotov, Serhii; Geryak, Yurii; Kavurka, Vitalii; Petrenko, Andrii; Brusentsova, Nataliia (Zootaxa, 2024)
In Ukraine, Emus hirtus Linnaeus, 1758 (Coleoptera: Staphylinidae) is protected by the national Red Book. The species is widely distributed in all natural zones of the country but occurs sporadically. Almost everywhere in Ukraine E. hirtus tends to decrease in abundance due to the reduction of pastures, a habitat to which this species is strictly specialized. Here we review all known records of E. hirtus in Ukraine summing up its distribution and bionomics in the country. We reflect on the possible causes of the population decline of this species and provide recommendations for its conservation in Ukraine and throughout its entire distribution range.